G230 Supporting parents ofchildren who have complex needs to assess and manage their children's pain: health care practitioners' perspectives. (27th April 2015) - Simons, JM; Carter, B; Bray, L; Arnott, J
Abstract : Aim: The aim of this paper is to present findings on the ways in which health care practitioners who work with children with complex needs can support parents in assessing and managing their child's pain. Methods: The data reported here are from semi-structured interviews undertaken with health care practitioners based at a tertiary children's hospital in the UK. These data are part of a larger mixed methods study. Data were analysed using thematic analysis. Results: Nineteen healthcare practitioners from a variety of disciplinary backgrounds (e.g. neurologists, nurses, physiotherapists) and with different experience (1–27 years) of working with children with complex needs participated in the study. Only one of the nineteen practitioners interviewed had had formal training on the management of pain in children with complex needs. Practitioners reported taking a multi-layered approach to managing pain in children with complex needs, which meant including parents, using skills of observation and referring to other members of the multidisciplinary team. The practitioners supported parents in the management of their child's pain by engaging with them, listening to them and also managing their expectations, although it was noted that parents' relationships with nurses could be problematic. Most practitioners felt parents had a central role in the management of their child's pain, although it was noted the role could vary and that the multidisciplinary team needed to provide opportunities for parents to give feedback. Practitioners felt that parents had a critical knowledge of their child's pain but not of pain itself. It was suggested that a critical knowledge of their child's pain takes time to develop and that some parents can misread pain cues. Most practitioners felt that parents did not receive adequate training and support to manage their child's pain. Conclusion: Practitioners value the knowledge of parents of children with complex needs and acknowledge the central role parents play in managing their child's pain. However, there is a need for practitioners to have formal education in the management of pain in children with complex needs so that they in turn can provide training and support for parents.